2019
DOI: 10.1097/apo.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Toxoplasmosis in a Tertiary Referral Center in Sydney Australia—Clinical Features, Treatment, and Prognosis

Abstract: Purpose: The aim of this study was to provide a retrospective analysis of the presentation, demographics, and treatment regimens for ocular toxoplasmosis at a large tertiary referral uveitis center. Design: Retrospective cohort study. Participants: A total of 48 patients with ocular toxoplasmosis who presented to Sydney Eye Hospital participated in this study. Methods: This is a retrospective review of patient file… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In line with this, the second study found no effect of ABs (Pyrimethamina and Sulfadiazine (PY/SA)) and corticosteroids on BCVA but on time to healing and recurrences compared to steroids alone [ 46 ]. The third study refers to a non-comparative case series treated with ABs (PY/SA) and corticosteroids and reported in the absence of a comparator a positive effect on BCVA and time to healing [ 47 ], which was confirmed by a British retrospective comparative case series that reported a shorter time to healing and less recurrences after 2 different AB treatments (Pyrimethamine and Spiramycin) compared to nothing or corticosteroids alone [ 48 ], and an Australian study using different antibiotics in combination with corticosteroids [ 53 ]. A French RCT compared systemic (PY/SA) and parabulbar antibiotics (Clindamycin) and found no difference in BCVA and time to healing [ 49 ].…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In line with this, the second study found no effect of ABs (Pyrimethamina and Sulfadiazine (PY/SA)) and corticosteroids on BCVA but on time to healing and recurrences compared to steroids alone [ 46 ]. The third study refers to a non-comparative case series treated with ABs (PY/SA) and corticosteroids and reported in the absence of a comparator a positive effect on BCVA and time to healing [ 47 ], which was confirmed by a British retrospective comparative case series that reported a shorter time to healing and less recurrences after 2 different AB treatments (Pyrimethamine and Spiramycin) compared to nothing or corticosteroids alone [ 48 ], and an Australian study using different antibiotics in combination with corticosteroids [ 53 ]. A French RCT compared systemic (PY/SA) and parabulbar antibiotics (Clindamycin) and found no difference in BCVA and time to healing [ 49 ].…”
Section: Resultsmentioning
confidence: 93%
“…Treatment outcome parameters ( Table 1 ) and outcomes were reported in 10 larger case series and clinical trials ( Table 2 [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]). Five of the 10 treatment studies referred to European and Northern American cohorts [ 45 , 46 , 47 , 48 , 49 ], two each to Iran [ 50 , 52 ] and Brazil [ 51 , 54 ] and one to Australia [ 53 ]. Two of four recurrence prophylaxis studies in immunocompetent individuals with OT came from Brazil, where the incidence and risk of recurrences are significantly higher, thus allowing us to analyze prophylactic strategies during a reasonable study period of 24 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations